Orbital prosthesis fabrication: current challenges and future aspects - Shrestha B; Thaworanunta S (Open Access Surgery, 2016)
Binit Shrestha, Sita Thaworanunta Maxillofacial Prosthetic Service, Department of Prosthodontics, Faculty of Dentistry, Mahidol University, Bangkok, Thailand Abstract: Orbital defect, arising from tumor-related resections, trauma, and congenital anomalies, can lead to negative functional and psychological effects in the patients. Rehabilitation with an orbital prosthesis can provide satisfactory aesthetic outlook and can be combined with surgical reconstruction to improve the retention. Despite less than ideal properties, silicone elastomer is the most commonly used material to fabricate orbital prosthesis. Several studies have been conducted on developing newer materials and improving the properties of silicone elastomer. Craniofacial implants offer greater retention compared to adhesives, but they have been observed to have a higher risk of implant failure and related side effects when placed in irradiated bone. This review gives a scope on understanding the current challenges faced during fabrication of orbital prosthesis and the future directions of this field. Keywords: orbital defect, silicone prosthesis, CAD/CAM, craniofacial implants